Mediating effect of job crafting dimensions on influence of burnout at self-efficacy and performance: revisiting health-impairment process of JD-R theory in public administration - Martínez-Díaz, Ana; Díaz-Fúnez, Pedro Antonio; Salvador-Ferrer, Carmen María; Hernández-Sánchez, Brizeida Raquel; Sánchez-García, José Carlos; Mañas-Rodríguez, Miguel Ángel (Frontiers in Psychology, 2023)
In recent years, job crafting has greatly interested Work and Organizational Psychology. Different research studies have shown its positive impact on people and organizational performance. However, it knows little about the differential effect of the two dimensions that make up this variable (promotion-focused and prevention-focused) and its role in the health-impairment spiral process of the job demand-resources theory (JD-R). This research aims to analyze the mediating effect of the different dimensions of job crafting on the influence of burnout on performance and self-efficacy in the workplace. The study used a sample of 339 administrative employees of a university. The results indicate that promotion-focused job crafting is a mediating variable in the relationship between the influence of burnout on performance and self-efficacy. Unexpectedly, prevention-focused job crafting does not have this mediating role in the same connection. These findings confirm the adverse impact of burnout on personal and organizational improvement while showing employees' absence of prevention/protection responses when burned out.